Review on Molecular Mechanisms of Antifouling Compounds: An Update since 2012 - Lianguo Chen; Pei-Yuan Qian (Marine Drugs, 2017)
Better understanding of the mechanisms of antifouling compounds is recognized to be of high value in establishing sensitive biomarkers, allowing the targeted optimization of antifouling compounds and guaranteeing environmental safety. Despite vigorous efforts to find new antifouling compounds, information about the mechanisms of antifouling is still scarce. This review summarizes the progress into understanding the molecular mechanisms underlying antifouling activity since 2012. Non-toxic mechanisms aimed at specific targets, including inhibitors of transmembrane transport, quorum sensing inhibitors, neurotransmission blockers, adhesive production/release inhibitors and enzyme/protein inhibitors, are put forward for natural antifouling products or shelf-stable chemicals. Several molecular targets show good potential for use as biomarkers in future mechanistic screening, such as acetylcholine esterase for neurotransmission, phenoloxidase/tyrosinase for the formation of adhesive plaques, N-acyl homoserine lactone for quorum sensing and intracellular Ca2+ levels as second messenger. The studies on overall responses to challenges by antifoulants can be categorized as general targets, including protein expression/metabolic activity regulators, oxidative stress inducers, neurotransmission blockers, surface modifiers, biofilm inhibitors, adhesive production/release inhibitors and toxic killing. Given the current situation and the knowledge gaps regarding the development of alternative antifoulants, a basic workflow is proposed that covers the indispensable steps, including preliminary mechanism- or bioassay-guided screening, evaluation of environmental risks, field antifouling performance, clarification of antifouling mechanisms and the establishment of sensitive biomarkers, which are combined to construct a positive feedback loop.